A Transcendental Exploration of Induction Training: Professional Development of College Science Teachers in Punjab - Ayaz Muhammad Khan, Yasir Hussain, Iqra Tariq (JSE, 2023)
Professional development is a continuous process that improves the working and learning skills of a person. This type of training and development should be started from the very initial stage of appointment of an employee. Teachers’ Professional development includes training that contributes to the development of knowledge, professional development in the field of a teacher’s expertise (Ramanan & Mohamad, 2021). Punjab Higher Education Commission engaged College teachers in a professional development program.